Interferon Regulatory Factor 8 Expressed in Microglia Contributes to Tactile Allodynia Induced by Repeated Cold Stress in Rodents - Takanori Akagi; Yuta Matsumura; Masaya Yasui; Emiko Minami; Hidemasa Inoue; Takahiro Masuda; Hidetoshi Tozaki-Saitoh; Tomohiko Tamura; Kazue Mizumura; Makoto Tsuda; Hiroshi Kiyama; Kazuhide Inoue (Elsevier, 2014)
Abstract.: We investigated the role of interferon regulatory factor 8 (IRF8) in a model of chronic pain in which repeated cold stress (RCS) exposure produces tactile allodynia. RCS exposure produced a decrease in paw withdrawal threshold (PWT) to mechanical stimulation. Spinal microglia of RCS-exposed mice were morphologically activated. Expression of IRF8 was significantly increased in the spinal cord of RCS-exposed mice and was localized in microglia. IRF8-knockout mice failed to show the RCS-induced decrease in PWT. Thus, RCS exposure activates spinal microglia and upregulation of IRF8 in these cells is involved in the development of tactile allodynia after RCS exposure. Keywords:: interferon regulatory factor-8, microglia, repeated cold stress